Torturous etiquettes film performance and social form - Varndell, Daniel, 1983- (Albany State University of New York Press, 2023)
Explores the ""torture"" of mannered behavior and the prevalence of etiquette as a theme in classical and contemporary Hollywood and European cinema.
Intro -- Contents -- List of Illustrations -- Acknowledgments -- Introduction: Minding Manners -- Speaking of Torture ... -- Performance, Inside-out -- Part I Initiation -- 1 Close Encounters: Greetings -- Say Thanks: Torturous Repetitions in Schindler's List -- You're in My Space: Territorial Offenses in Cape Fear -- Do You Mind? Codeswitching in Frost/Nixon -- Hands Off: Contamination Fears in Philadelphia -- You People ... : Speech Violations in The Irishman -- 2 Home Invasions: Hospitality -- Rooms within Rooms: Romeo and Juliet and Beguiled -- Host(age): Funny Games -- Frontiers of Shame: The Girl with the Dragon Tattoo -- Acknowledging Harry: A Bigger Splash -- 3 Crossing the Line: Embarrassment -- Risky Banter in Gran Torino -- Badly Done in Emma -- Part II Exchange -- 4 No Joke: Humor -- Mistiming in I Love You Phillip Morris -- Mis-staging in Chinatown -- Misunderstanding in Goodfellas -- 5 The Butler Did It: Service -- Hand over the Table: Jezebel -- Profaning the Table: Breaking Bakhtin's "Third Person" -- The Dignity of The Butler -- 6 Racist Etiquette: Disservice -- Volte-face: In the Heat of the Night -- White Looks: Ma Rainey's Black Bottom -- Author's Note -- Part III Dissolution -- 7 Garments of the Mind: Clothes -- Playing a Gentleman: Our Man in Havana -- Born Gentlemen: DiCaprio's Conmen -- A Burst of Color: Will Smith in Six Degrees of Separation -- Offending the Definitions: On Wearing Red -- Seeing Red in Jezebel -- 8 Tabular Outrages: Dinner -- Governed Appetites: Norbert Elias's Civilizing Process -- Tabular Desecration: Hannibal -- An Improper Attack: American History X -- Dine with Me: Edward Scissorhands, Greystoke, and Babette's Feast -- 9 Tresses and Distresses: Intimacy -- Tresses: Fixing -- Distresses: Scalping -- Conclusion: As Time Goes By
Includes bibliographical references and index.
JSTOR
Keywords: Etiquette in motion pictures; Motion pictures -- United States; Motion pictures -- Europe; Cinéma -- États-Unis.; PERFORMING ARTS / Film & Video / History & Criticism; Motion pictures; Europe; United States